The Demise, Dissolution and Elimination of Religions - Stausberg, Michael (Numen, 2021)
Abstract While it is generally acknowledged that religions can “die” or go “extinct,” little research has been dedicated to the problem of the demise of religions. This text reviews earlier research on this topic and develops some reflections on two types of religion (ethno-specific and transcendental ones) and on the end of indigenous religions. The text stresses the importance of ruler conversions and indigenous agency in religion demise and transformation processes, introduces the category of “religiocide,” and proposes some criteria for identifying “religion death.” Finally, it introduces the articles of this special issue.